Identification of Leptospira Bacteria in Human Urine According to Islamic View - Satryanto, Muslimin Budiman; Widiyanti, Dian; Karimulloh, Karimulloh (UNUSA Press, 2020)
Leptospirosis is a zoonotic infectious disease caused by pathogenic organisms belong to the genus Leptospira, which are transmitted directly or indirectly from animals to humans. Most countries in the Southeast Asia regions are endemic for leptospirosis. The incidence of leptospirosis is strongly influenced by various socio-cultural, occupational, behavioral, and environmental factors. The amount of risk depends on the prevalence of Leptospira in the local area and the frequency of exposure. One of the tests to confirm the diagnosis of leptospirosis is by isolating Leptospira bacteria with culture and molecular examination of a person's body fluid specimens such as blood, cerebrospinal fluid, or urine. To identify Leptospira bacteria in leptospirosis cases in humans, urine samples can be used. This examination is the development of methods used in medical science to diagnose leptospirosis. One of the verses in the Qur’an regarding science is